Applications of Kinematic GPS at SHOM - Even, Michel (The International Hydrographic Review, 2018)
The GPS in kinematic mode has now been in use at SHOM for several years in geodetic work. During the past year, these applications have been extended to include position-fixing during hydrographic surveys, thanks to the realtime function. Today, exploitation of the vertical component offers new perspectives, notably for tidal observations.